Management of educational practice in ambushesm cooperation and partnership as a condition of professional self-realization of future engineers - Ануфрієва, О. Ф. (Scientific notes of the pedagogical department, 2017)
The article examines the processes of management teaching practices at the level of organization of pedagogical interaction between the participants of the educational process, it encourages them to professional self-realization, getting the experience of self-management. It is noted that the formation of professional self-realization depends on well-chosen educational practice management techniques. The notion of "management training practices of future engineers" as stimulating the development of professional self-realization of the future engineers, the formation of the students' abilities to collaborate and interact with each other.